2008
DOI: 10.1002/anie.200704539
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Synthetic Potential of Asymmetric Deprotonation: Arylation of Carbanions

Abstract: arylations · asymmetric synthesis · carbanions · Negishi coupling · transmetalation Forover15 years, synthetic organic chemists have had access to enantioenriched carbanions derived from N-Boc pyrrolidine 1 (Boc = tert-butoxycarbonyl) and O-alkyl carbamates 2 upon treatment with a chiral base comprising sBuLi and (À)-sparteine (Scheme 1). [1,2] This asymmetric deprotonation methodology was pioneered by the groups of Hoppe and Beak, [1][2][3] and has been supplemented by work in which a readily accessible (+)-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…Aggarwal et al have shown that the direct reaction of lithiated carbamates with boranes and boronic esters shows considerable scope and therefore potential for synthesis (Table 4). In all cases high enantioselectivities were observed (er 95 : 5–98 : 2) 30,31…”
Section: Direct Reaction Of Lithiated Carbamates With Boronic Esters mentioning
confidence: 84%
“…Aggarwal et al have shown that the direct reaction of lithiated carbamates with boranes and boronic esters shows considerable scope and therefore potential for synthesis (Table 4). In all cases high enantioselectivities were observed (er 95 : 5–98 : 2) 30,31…”
Section: Direct Reaction Of Lithiated Carbamates With Boronic Esters mentioning
confidence: 84%
“…[1] The importance of this motif to such a broad spectrum of chemistry has prompted the development of a range of methodologies for its synthesis which include Sharpless aminohydroxylation [2] as well as the addition of nucleophiles to aminocarbonyls, [3] imines, [4] epoxides, and aziridines. [5] We considered a conceptually different route to prepare this class of compound: namely, the lithiation/borylation [6] of aziridines [7] (Scheme 1, pathway a).This route was attractive because: 1) it combines readily available aziridines 1 and boronic esters 2, and creates a C À C bond, 2) high stereoselectivity for the overall process could be expected since lithiation of N-Boc [8] (tert-butoxycarbonyl) and N-Bus [9] (tert-butylsulfonyl) aziridines [10] had been shown to occur trans to the aziridine substituent, and the subsequent steps (3 ! 4 !…”
mentioning
confidence: 99%
“…[1] The importance of this motif to such a broad spectrum of chemistry has prompted the development of a range of methodologies for its synthesis which include Sharpless aminohydroxylation [2] as well as the addition of nucleophiles to aminocarbonyls, [3] imines, [4] epoxides, and aziridines. [5] We considered a conceptually different route to prepare this class of compound: namely, the lithiation/borylation [6] of aziridines [7] (Scheme 1, pathway a).…”
mentioning
confidence: 99%
“…[1] The importance of this motif to such a broad spectrum of chemistry has prompted the development of a range of methodologies for its synthesis which include Sharpless aminohydroxylation [2] as well as the addition of nucleophiles to aminocarbonyls, [3] imines, [4] epoxides, and aziridines. [5] We considered a conceptually different route to prepare this class of compound: namely, the lithiation/borylation [6] of aziridines [7] (Scheme 1, pathway a).This route was attractive because: 1) it combines readily available aziridines 1 and boronic esters 2, and creates a C À C bond, 2) high stereoselectivity for the overall process could be expected since lithiation of N-Boc [8] (tert-butoxycarbonyl) and N-Bus [9] (tert-butylsulfonyl) aziridines [10] had been shown to occur trans to the aziridine substituent, and the subsequent steps (3 ! 4 !…”
mentioning
confidence: 99%
“…[1] The importance of this motif to such a broad spectrum of chemistry has prompted the development of a range of methodologies for its synthesis which include Sharpless aminohydroxylation [2] as well as the addition of nucleophiles to aminocarbonyls, [3] imines, [4] epoxides, and aziridines. [5] We considered a conceptually different route to prepare this class of compound: namely, the lithiation/borylation [6] of aziridines [7] (Scheme 1, pathway a).…”
mentioning
confidence: 99%